STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN - Lestari, Adinda Zalva; Nurochim, H; Kusumaningrum, Hesti (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
The principal plays a crucial role in increasing the quality of education through effective organizational management and professional development of teachers. This study analyzes the strategies implemented by school principals to enhance educational quality, emphasizing the significance of resource management and adapting to external trends such as globalization and technological advancements. Using a literature review methodology, the study collects and synthesizes existing research to highlight the relationship between principal leadership and educational outcomes. The findings indicate that successful principals build strong collaboration with teachers and parents, ensure compliance with national education standards, and implement continuous improvement plans. Additionally, fostering a positive school environment and professional growth for educators are pivotal in achieving educational excellence. Ultimately, effective leadership strategies are essential in navigating challenges and improving the overall quality of education..